SPI1-mediated macrophage polarization aggravates age-related macular degeneration - Qi, Siyi; Zhang, Yihan; Kong, Lingjie; Bi, Daode; Kong, Hongyu; Zhang, Shujie; Zhao, Chen (Frontiers in Immunology, 2024)
Objective: This study revealed a core regulator and common upstream mechanisms for the multifaceted pathological processes of age-related macular degeneration (AMD) and provided proof-of-concept for this new therapeutic target.Methods: Comprehensive gene expression analysis was performed using RNA sequencing of eye cup from old mice as well as laser-induced choroidal neovascularization (CNV) mouse model. Through integrative analysis and proteinprotein interaction (PPI) analysis, common pathways and key transcription factor was identified simultaneously engaged in age-related retinal degeneration and CNV, the two typical pathological process of AMD. Subsequently, the expression changes of Spi1, the key regulator, as well as the alternation of the downstream mechanisms were validated in both models through qRT-PCR, Elisa, flow cytometry and immunofluorescence. Further, we assessed the impact of Spi1 knockdown in vitro and in vivo using gene intervention vectors carried by adeno-associated virus or lentivirus to test its potential as a therapeutic target.Results: Compared to corresponding controls, we found 1,939 and 1,319 genes differentially expressed in eye cups of old and CNV mice respectively. The integrative analysis identified a total of 275 overlapping DEGs, of which 150 genes were coupregulated. PPI analysis verified a central transcription factor, SPI1. The significant upregulation of Spi1 expression was then validated in both models, accompanied by macrophage polarization towards the M1 phenotype. Finally, SPI1 suppression significantly inhibited M1 polarization of BMDMs and attenuated neovascularization in CNV mice.This study demonstrates that SPI1 exerts a pivotal role in AMD by regulation of macrophage polarization and innate immune response, offering promise as an innovative target for treating AMD.